Organic solar cell device prepared by shear coating of solution assisted by electric field and preparation method of organic solar cell device
By using an external pulsed polarized electric field to regulate molecular arrangement during the preparation of the active layer of organic solar cells, the problem of unsatisfactory microcrystalline morphology in the green solvent solution shearing process was solved, achieving efficient photoelectric conversion and improved stability, laying the foundation for the commercialization of organic photovoltaic technology.
Patent Information
- Application Number
- CN202410868743.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2026-01-06
AI Technical Summary
In organic solar cells fabricated using air-solution shearing with green solvents, the non-ideal microcrystalline morphology limits the photovoltaic efficiency and stability of the devices, making it difficult to achieve efficient commercial applications.
The microcrystalline morphology of the organic photovoltaic active layer is controlled by an external pulsed polarized electric field. By controlling the torque of the molecular dipole by the polarized electric field, the orientation control of the upward-facing microcrystalline morphology is achieved, forming a long-range ordered upward-facing small molecule acceptor fibrous morphology.
It improves the photoelectric conversion efficiency and device stability of organic solar cells, reduces the environmental impact of the fabrication process, and promotes the commercialization of organic photovoltaic technology.
Smart Images

Figure CN121285154A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an organic solar cell device and its preparation method prepared by electric field-assisted solution shear coating, and to the preparation and application of high-efficiency organic solar cell devices by solution shear coating in air, belonging to the field of organic photovoltaic device preparation technology. Background Technology
[0002] Against the backdrop of global energy structure transformation, organic solar cells have gradually become an important branch of promoting clean and renewable energy, low-carbon economy, and green finance. Organic solar cells fabricated using solution processing methods possess numerous unique advantages not found in inorganic semiconductor photovoltaic cells, such as thinness, flexibility, semi-transparency, wearability, and roll-to-roll printing capabilities. In recent years, the power conversion efficiency of organic photovoltaic devices based on non-fullerene small molecule acceptors has exceeded 19%, but this still lags behind the nearly 26% efficiency of traditional silicon-based solar cells. Furthermore, compared to the traditional crystalline silicon photovoltaic industry, organic photovoltaic cells still have many opportunities for improvement in areas such as long-term device stability, large-area device fabrication for commercialization, and cost control. Focusing on the unique characteristics of organic photovoltaics, air-processable organic photovoltaic fabrication processes based on green solvents have become a hot research area for promoting the industrialization of organic photovoltaics in recent years. Green solvent-based organic photovoltaic fabrication processes reduce the adverse environmental impact of harmful chemicals. In addition, air-processable fabrication processes lower the cost of renewable energy and enhance the competitiveness of organic photovoltaic cells. However, the complex process of solution shear film formation kinetics limits the micromorphology of the active layer of organic photovoltaics, restricting further improvements in their power conversion efficiency. Based on the research results published globally, the power conversion efficiency of air-processable organic photovoltaic devices based on green solvents has room for improvement compared with the power conversion efficiency of organic solar cells prepared by spin coating in inert gases based on low-boiling-point solvents. This is due to the non-ideal microcrystalline morphology structure caused by the crystallization behavior of donors and acceptors in the active layer.
[0003] The microcrystalline morphology of the donor and acceptor components within the active layer can modulate exciton diffusion and dissociation, as well as carrier transport and extraction, which further influences the overall performance of photovoltaic devices. Ideally, the active layer microcrystalline morphology involves both donor and acceptor molecules adopting an upward orientation, meaning the principal orientation of the molecules in the organic semiconductor material is perpendicular to the device surface, and the acceptor molecules form an ordered 3D network stack. This upward orientation facilitates easier transitions of electrons and holes between molecules along the vertical direction in organic photovoltaic devices, thereby improving charge separation and transport efficiency. Furthermore, when the principal axis of the molecules is perpendicular to the incident light, photons more easily excite electron-hole pairs within the molecules, thus improving photoelectric conversion efficiency and enabling the device to convert light energy into electrical energy more efficiently. Additionally, the upward orientation is generally related to the crystal quality and stability of organic semiconductor materials. Materials with better crystal orientation tend to form stable lattice structures, which helps reduce defects and interface effects in the material, thereby improving the long-term performance stability of the device. In summary, upward-facing crystal orientation contributes to improved charge separation, photoelectric conversion efficiency, and device performance stability in organic photovoltaics, thus playing a crucial role in optimizing device performance and advancing organic photovoltaic technology. Researching and controlling crystal orientation is one of the key aspects of designing and fabricating air-solution-shear-processable organic photovoltaic devices based on green solvents. Summary of the Invention
[0004] To address the non-ideal microcrystalline morphology in solar cells currently fabricated using green solvent solution shearing processes, this invention provides an organic photovoltaic device and its fabrication method that utilizes electric field modulation for molecular alignment and air solution shearing coating to overcome these shortcomings. This method is simple to operate and has a certain degree of universality.
[0005] This invention selects an organic solar active layer based on a non-fullerene acceptor, which currently boasts high photoelectric conversion efficiency, as the intrinsic system. The polymer donor material is PM6, and the non-fullerene acceptor material is BTP-eC9. Furthermore, a halogen-free solvent, o-xylene, is used as the green solvent chosen in this invention. The active layer coating strategy, employing electric field modulation for molecular alignment and air-solution shear coating, utilizes an externally applied pulsed polarized electric field to control the stacking and microcrystalline morphology of donor and acceptor molecules in the active layer during the coating process. This method achieves the orientation of the dipole orientation of organic photovoltaic molecules, especially non-fullerene acceptor molecules, by the electric field during the solution shear coating film formation of the photovoltaic active layer based on an environmentally friendly green solvent. By leveraging the torque of the polarized electric field on the molecular dipoles, the upward-facing microcrystalline morphology of the active layer is controlled. This includes the formation of long-range ordered, upward-facing small molecule acceptor fibrous morphology, significantly improving the efficiency of organic photovoltaic devices based on air-solution shear coating using green solvents. In summary, the microcrystalline structure of organic photovoltaic semiconductors in the solution shear coating process controlled by an externally polarized electric field provided by this invention offers a detailed solution for the commercialization of organic solar cells and has excellent prospects for industrialization and commercial application.
[0006] Terminology Explanation:
[0007] 1. PM6 is a polymer material with the molecular formula:
[0008] Poly[(2,6-(4,8-bis(5-(2-ethylhexyl)-4-fluorothiophen-2-yl)benzo[1,2-b:4,5-b']dit hiophene))-co-(1,3-di(5-thiophene-2-yl)-5,7-bis(2-ethylh-exyl)-benzo[1,2-c:4,5-c']dithiophene-4,8-dione] is mainly used as a donor material for organic solar cells.
[0009] 2. BTP-eC9 is a non-fullerene photovoltaic material with the molecular formula:
[0010] 2,2′-((2Z,2′Z)-((12,13-bis(2-butyloctyl)-3,9-dinonyl12,13-dihydro-[1,2,5]thiad iazolo[3,4-e]thieno[2″,3″:4′,5′]thieno[2′,3′:4,5]pyrrolo[3,2-g]thieno[2′,3′:4,5]thieno[3,2-b]indole-2,10-diyl)bis
[0011] (methaneylylidene))bis(5,6-dichloro-3-oxo-2,3-dihydro-1H-indene-2,1-diylidene))dimalononitrile is mainly used as the acceptor material for organic solar cells.
[0012] 3. PDINN is a polymer photovoltaic material, Aliphatic amine-functionalized Perylene-diimide, mainly used as an electron transport layer material in organic solar cells.
[0013] 4. PEDOT:PSS is a polymer photovoltaic material with the molecular formula:
[0014] Poly(3,4-ethylenedioxythiophene): Poly(styrene sulfonate) is mainly used as a hole transport layer material in organic solar cells.
[0015] The technical solution of the present invention is as follows:
[0016] An organic solar cell device fabricated using electric field-assisted solution shear coating comprises, from bottom to top, a glass substrate, an indium tin oxide transparent conductive film (anode), a PEDOT:PSS hole transport layer, an organic photosensitive active layer, a PDINN electron transport layer, and a top silver electrode (cathode). The organic photosensitive active layer includes a polymer donor material and a non-fullerene acceptor material. Electric field modulation for molecular alignment and air-based solution shear coating are the fabrication processes for the active layer in this organic solar cell device. The anode and cathode are the two metal electrodes of the cell structure, also referred to as the positive and negative electrodes. Except for the active layer, the fabrication processes for all other layers are consistent with those in conventional organic solar cells.
[0017] According to a preferred embodiment of the present invention, the polymer donor material in the organic photosensitive active layer is PM6, and the non-fullerene acceptor material is BTP-eC9, with a mass ratio of 1:1.2.
[0018] This invention relates to an organic photovoltaic active layer fabrication technology based on the aforementioned air-polarized electric field used for organic solution shear coating. The active layer in an organic photovoltaic device is fabricated using the aforementioned photovoltaic material: an active layer solution is coated onto a hole transport layer using a solution shear coating machine (scalpel coater) under the assistance of an applied polarized electric field, thus obtaining the active layer in the organic photovoltaic device. The applied electric field is achieved by connecting the doctor blade of the solution shear coating machine to the substrate stage using a pulsed polarized voltage source (10V-10kV, 200Hz). This active layer fabrication technology allows for the optimization of the microcrystalline structure of the donor material PM6 and the acceptor material BTP-eC9 molecules in the photosensitive active layer, and the manipulation of the vertical distribution of donor and acceptor components within the photosensitive active layer based on solvent polarity. The vertical direction is perpendicular to the glass substrate.
[0019] According to a preferred embodiment of the present invention, an ITO transparent conductive film is attached to the glass substrate, which is a transparent conductive substrate; the ITO transparent conductive film has a thickness of 130 nm; the hole transport layer material is PEDOT:PSS with a thickness of 30 nm; the organic photosensitive active layer has a thickness of 120 nm; the electron transport layer material is PDINN with a thickness of 5 nm; and the top electrode material is silver (Ag) with a thickness of 100 nm.
[0020] The fabrication method of the organic solar cell device prepared by electric field-assisted solution shear coating includes the following steps:
[0021] (1) Clean the transparent conductive substrate, wherein the transparent conductive substrate is a glass substrate with an ITO transparent conductive film attached;
[0022] (2) A hole transport layer PEDOT:PSS thin film is prepared on the transparent conductive substrate obtained in step (1) using conventional preparation methods;
[0023] (3) Preparation of organic active layer thin films, including:
[0024] a. Weigh a total of 10 mg PM6 and 12 mg BTP-eC9 using a high-precision electronic balance (readability 0.01 mg, weighing range 0.02-30 mg) and mix them. Then add 1 mL of high-purity o-xylene solvent (AR > 99%) to the weighed mixture and place it on a heatable magnetic stirrer. Stir at 80 °C for 2.5 h to obtain a PM6:BTP-eC9 blend solution with a total concentration of 22 mg / mL.
[0025] b. Using a high-precision pipette (readability 0.01 μL), add 2.50 μL of 1,8-diiodooctane additive to the PM6:BTP-eC9 blend solution obtained above, and continue stirring for 30 min to obtain a fully dissolved mixed solution with a PM6:BTP-eC9 mass ratio of 1:1.2.
[0026] c. In an air environment (relative humidity 40%), the mixed solution prepared in step b is coated onto the substrate with hole transport layer obtained in step (2) using a blade coater under the action of an external pulsed polarized electric field (voltage source value 10V-1kV).
[0027] In step (3), at this solution concentration and corresponding stirring temperature, all components can be fully dissolved in the chloroform solvent;
[0028] (4) Deposit an electron transport layer PDINN thin film on the organic photosensitive active layer;
[0029] (5) The metal electrode material is deposited on the electron transport layer by vapor deposition.
[0030] Preferably, in step c of step (3), the external pulsed polarization electric field is applied by using a pulsed polarization voltage source (10V~10kV, 200Hz) connected to the scraper and substrate stage of the solution shear coating machine.
[0031] According to a preferred embodiment of the present invention, in step c of step (3), when the active layer solution is applied by scraping, the substrate temperature is 80°C, the gap between the scraper and the substrate is 150 μm, the moving speed of the scraper relative to the substrate is 25 mm / s, the amount of mixed solution used in the slit between the scraper and the substrate is 30 μL, and the thickness of the active layer obtained under these conditions is 120 nm.
[0032] Preferably, in step c of step (3), the voltage provided by the pulse power supply is 10-10kV, 200Hz, square wave, and duty cycle 1-99%. More preferably, in step c of step (3), the voltage provided by the pulse power supply is 100V, 200Hz, square wave, and duty cycle 50%. Under these conditions, the organic active layer can form a fibrous interconnect morphology, thereby improving the photoelectric conversion efficiency of the corresponding device.
[0033] Preferably, in step (1), the transparent conductive substrate (i.e., the glass substrate with ITO transparent conductive film) is sequentially ultrasonically cleaned in an ultrasonic machine with precision electrical cleaner, deionized water, acetone, anhydrous ethanol and isopropanol for 10 minutes each. After cleaning, it is dried with high-purity nitrogen (purity > 99%). The dried transparent conductive substrate is then placed in an ultraviolet ozone cleaner and cleaned for 30 minutes.
[0034] Preferably, in step (2), a hole transport layer material PEDOT:PSS with a thickness of 30 nm is spin-coated onto a cleaned transparent conductive substrate in air using a spin coater, and then the substrate with the spin-coated hole transport layer material is placed on a hot plate at 150°C and annealed for 15 min.
[0035] Preferably, in step (4), PDINN is dissolved in high-purity methanol solvent (AR > 99%, concentration 1.5 mg / mL), the pre-prepared PDINN solution is placed on a magnetic stirrer and stirred at room temperature for 2 hours to obtain a fully dissolved PDINN solution; the fully dissolved PDINN solution is spin-coated onto the organic photosensitive active layer that has been annealed in step (3) using a spin coater.
[0036] Preferably, in step (5), the substrate with hole transport layer / organic photosensitive active layer / electron transport layer obtained in step (4) is moved into the physical vapor deposition chamber, and after starting the vacuum system, the chamber pressure is reduced to 2.5 × 10⁻⁶. - 4 Pa is used to heat a silver target to prepare an Ag electrode on a substrate with a thickness of 100 nm.
[0037] The advantage of this air-polarized electric field-based active layer preparation technology for organic solution shear coating lies in its ability to achieve contactless control of molecular crystallization orientation and crystallization mode within the active layer using a controllable external electric field without adding steps to conventional preparation methods. This is achieved through the control of molecular crystallization orientation and crystallization mode within the active layer.
[0038] The beneficial effects of this invention are as follows:
[0039] Based on the current traditional solution shear coating technology, this invention achieves improved efficiency, stability, and commercial application prospects of photovoltaic devices while maintaining environmental protection and sustainability. The technology has the following advantages: (1) Improved photovoltaic device efficiency: Through electric field modulation technology, the active layer of organic solar cells can form an upward-facing microcrystalline structure, thereby improving charge separation and transport efficiency. This helps increase the photoelectric conversion efficiency of photovoltaic devices, enabling them to more effectively convert light energy into electrical energy. (2) Environmental protection and sustainability: Using green solvents and environmentally friendly preparation methods reduces the adverse environmental impact of harmful chemicals. This aligns with the environmental protection and sustainable development goals of the dual-carbon strategy, contributing to the promotion of clean energy and a low-carbon economy. (3) Improved device stability: By regulating the microcrystalline structure, the device stability of organic solar cells is improved. A better microcrystalline structure helps reduce defects and interface effects in the material, thereby increasing the long-term performance stability of the device. (4) Commercial application prospects: Detailed preparation methods are provided, offering solutions for the commercialization of organic solar cells. This helps promote the advancement of organic photovoltaic technology and enhances the competitiveness of organic solar cells in the renewable energy market. In summary, this technology is expected to have a positive impact on improving solar cell efficiency, reducing the environmental impact of the fabrication process, enhancing device stability, and promoting commercial applications, thus contributing to the development of the clean energy sector. Attached Figure Description
[0040] Figure 1 This invention relates to a method for fabricating organic solar cell devices using electric field-assisted solution shear coating.
[0041] Figure 2 for Figure 1 Enlarged view of the area within the middle circle;
[0042] Figure 3 for Figure 1 A schematic diagram of the pulse voltage waveform used;
[0043] Figure 4 The photovoltaic response curve obtained from Example 2 is shown.
[0044] Figure 5 The distribution morphology of receptor material on the sample surface obtained in Example 3;
[0045] Figure 6 The photovoltaic response curve obtained from the test in Comparative Example 1;
[0046] Figure 7 The distribution morphology of receptor material on the sample surface obtained from the test of Comparative Example 2 is shown. Detailed Implementation
[0047] To make the technical problems, solutions, and advantages of this invention clearer, a detailed description will be provided below with reference to the accompanying drawings and specific embodiments. Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in this invention can be purchased commercially or prepared by existing methods. This invention addresses existing problems by providing a method for preparing high-efficiency organic solar cell devices using electric field modulation technology for shear coating of solutions in air. The preparation method, the pulse voltage waveform used, and the effects are illustrated below. Figure 1-7 As shown.
[0048] Example 1:
[0049] An organic solar cell device fabricated by electric field-assisted solution shear coating comprises, from bottom to top, a glass substrate, an indium tin oxide transparent conductive film (anode), a hole transport layer, an organic photosensitive active layer, an electron transport layer, and a top metal electrode (cathode). Figure 1 As shown, the method for preparing the organic photosensitive active layer is the same as the method described in this invention for preparing high-efficiency organic solar cell devices using electric field modulation technology for solution shear coating in air. The organic photosensitive active layer comprises a polymer donor and a non-fullerene acceptor.
[0050] A glass substrate with an ITO transparent conductive film is a transparent conductive substrate, wherein the ITO thickness is 130 nm and the sheet resistance is <15 Ωcm. -2 The hole transport layer is a polymer PEDOT:PSS with a thickness of 30 nm, the electron transport layer is PDINN with a thickness of 5 nm, and the top metal electrode is silver (Ag) with a thickness of 100 nm.
[0051] The polymer donor is PM6, and the non-fullerene acceptor is BTP-eC9. The method for fabricating high-efficiency organic solar cell devices using air-based solution shear coating with electric field modulation technology is an organic photosensitive active layer preparation strategy. The preparation process includes: applying a pulsed voltage between a doctor blade and a substrate, and depositing a 120nm thick mixed material film on the hole transport layer by shearing a PM6:BTP-eC9 mixed solution with the doctor blade.
[0052] The mass ratio of the two materials in the PM6:BTP-eC9 mixed solution is 1:1.2, and the pulse voltage is 100V.
[0053] The use of pulsed electric field modulation technology in the preparation of organic photosensitive active layer has resulted in a relatively ideal microcrystalline morphology and vertical component distribution of the two materials. This has solved the problem of limited efficiency in the preparation of organic solar cells in air and eliminated the post-annealing step, providing a new approach for the industrialization of organic photovoltaics in the future.
[0054] Example 2
[0055] A method for preparing an organic solar cell device using electric field-assisted solution shear coating as described in Example 1 includes the following steps:
[0056] (1) Cleaning the transparent conductive substrate: The transparent conductive substrate (i.e., the glass substrate with ITO transparent conductive film) is ultrasonically cleaned in an ultrasonic machine for 10 minutes each with precision electrical cleaner, deionized water, acetone, anhydrous ethanol and isopropanol. After cleaning, it is dried with high-purity nitrogen (>99%). The dried transparent conductive substrate is placed in an ultraviolet ozone cleaner and cleaned for 30 minutes.
[0057] (2) Preparation of hole transport layer: In air, using a KW-5 spin coater from the Institute of Microelectronics, Chinese Academy of Sciences, a hole transport layer material PEDOT:PSS with a thickness of 30 nm was spin-coated onto a cleaned transparent conductive substrate. Then, the substrate with the hole transport layer material was placed on a hot plate at 150°C and annealed for 15 min. PEDOT:PSS was purchased from Xi'an Baolai Technology Co., Ltd. Before use, PEDOT:PSS was diluted with ultrapure water at a ratio of 1:1 and stirred in the dark on a magnetic stirrer at room temperature for 30 min.
[0058] (3) Preparation of the organic photosensitive active layer: The PM6:BTP-eC9 blend was dissolved in high-purity o-xylene solvent (AR > 99%, concentration 22 mg / mL). The preliminarily prepared solution was placed on a magnetic stirring heating table and stirred at 80℃ for 2.5 h to obtain a fully dissolved solution. Using a high-precision pipette (readability 0.01 μL), 2.50 μL of 1,8-diiodooctane additive was added to the obtained PM6:BTP-eC9 blend solution. After continuing to stir, P was obtained. M6: BTP-eC9 mass ratio of 1:1.2 mixed solution; in an air environment (relative humidity 40%), the mixed solution is coated onto the substrate after annealing in step (2) using a solution shearing coater under the action of an external pulsed polarized electric field (voltage source value is 100V). The moving speed of the scraper is 25mm / s, the substrate stage temperature is 80℃, and the photovoltaic material molecules inside the solution on the substrate are regulated by the pulsed electric field during the curing process, exhibiting an upward microcrystalline orientation and fibrous acceptor small molecule crystal morphology;
[0059] (4) Preparation of electron transport layer: PDINN is dissolved in high-purity methanol solvent (AR>99%, concentration is 1.5mg / mL), the preliminarily prepared PDINN solution is placed on a magnetic stirring table and stirred at room temperature for 2h to obtain a fully dissolved PDINN solution; the fully dissolved PDINN solution is spin-coated onto the organic photosensitive active layer after annealing in step (3) using a spin coater.
[0060] (5) Fabrication of metal electrodes: The substrate with hole transport layer / organic photosensitive active layer / electron transport layer obtained in step (4) is transferred into the physical vapor deposition chamber. After starting the vacuum system, wait for the chamber pressure to drop to 2.5 × 10⁻⁶. -4 Pa is used to heat a silver target to prepare an Ag electrode on a substrate with a thickness of 100 nm.
[0061] The detailed steps for preparing the organic photosensitive active layer in step (3) above are as follows:
[0062] a. Weigh the polymer donor and non-fullerene acceptor using a high-precision electronic balance (readable 0.01 mg, weighable range 0.02-30 mg). Weigh 10.0 mg of the polymer donor PM6 (Solarmer, >99%) and place it in a glass sample vial. Weigh 12 mg of the non-fullerene acceptor BTP-eC9 (Solarmer, >99%) and place it in the glass sample vial. The mass ratio of PM6:BTP-eC9 in the sample vial is 1:1.2.
[0063] Place the glass sample vial in a nitrogen-protected glove box. Under a nitrogen atmosphere, add 1 mL of high-purity o-xylene solvent (Sigma Aldrich, AR > 99%) to the sample vial. Place it on a magnetic stirrer and heat and stir at 80°C for 2.5 h to obtain a fully dissolved mixed solution containing organic photovoltaic materials with a concentration of 22 mg / mL.
[0064] b. Under a nitrogen atmosphere, add 1,8-diiodooctane additive (Sigma Aldrich, >99%) to the obtained sample vial solution at a ratio of 0.25% vol, and continue stirring for 30 min before using it to prepare the active layer by scraping the solution.
[0065] c. In air (relative humidity 40%), apply a 100V pulse voltage (square wave, frequency 200Hz, duty cycle 50%) between the doctor blade and the substrate stage in the doctor blade coater using a pulse voltage source. Use the doctor blade coater to shear and coat the mixed solution prepared in step c onto the PEDOT:PSS hole transport layer, as shown. Figure 1-3As shown, the substrate temperature of the substrate in the doctor blade coating apparatus is set to 80℃, the slit height between the doctor blade and the substrate is 150μm, the moving speed of the doctor blade relative to the substrate is 25mm / s, and the amount of mixed solution used in the slit between the doctor blade and the substrate is 30μL, resulting in an organic photosensitive active layer with a thickness of 120nm.
[0066] In traditional blade shearing solution deposition for preparing organic photosensitive active layers, solvent evaporation leads to unfavorable crystal sizes in the donor-acceptor and mixed domains, hindering effective dissociation of photoexcitons and extraction of photogenerated charges. However, the electric field modulation technique described in this invention, used in the fabrication of high-efficiency organic solar cell devices via air-based solution shearing coating, employs a pulsed electric field. This pulsed electric field enables nanoscale crystallization manipulation of organic photovoltaic materials during solvent evaporation within the mixed solution, particularly for acceptor molecules, forming continuous nanofiber-like crystal morphologies. This facilitates the formation of a bicontinuous fibrous interpenetrating network between donors and acceptors in the organic photosensitive active layer, as well as the dissociation of photoexcitons and the extraction of photogenerated charges. The prepared organic photovoltaic device was tested under AAA solar simulator illumination. The solar simulator spectral distribution was AM1.5G, and the illumination intensity was calibrated to 100 mW / cm² using a standard silicon cell. 2 The open-circuit voltage (V) of the device was measured under the above conditions. OC ) = 0.851V, short-circuit current (J) SC = 26.3 mA / cm 2 The fill factor (FF) is 76.7%, and the photoelectric conversion efficiency (PCE) is 17.4%. Figure 4 As shown.
[0067] Example 3
[0068] Organic photovoltaic devices are prepared according to the device structure described in Example 1 and the method for preparing high-efficiency organic solar cell devices using electric field modulation technology for solution shear coating in air as described in Example 2, with the following differences:
[0069] Without performing step (5), the resulting device structure from top to bottom is: electron transport layer (PDINN, 5nm), all-polymer photosensitive active layer (100nm), hole transport layer (PEDOT:PSS, 30nm), ITO (130nm), and glass substrate.
[0070] The distribution morphology of the acceptor components on the surface of the photosensitive active layer was observed using light-induced atomic force microscopy, such as... Figure 5 As shown, the non-fullerene small molecule acceptor material forms a continuous network of fiber-like morphology in the organic photosensitive active layer under the induction of a pulsed electric field, which plays a positive role in the dissociation of photogenerated excitons and the transport and extraction of photogenerated charges.
[0071] Comparative Example 1
[0072] Based on the device structure described in Example 1 and the method for preparing high-efficiency organic solar cell devices using electric field modulation technology for solution shear coating in air as described in Example 2, an organic photovoltaic device was prepared. The difference is that in step (3), a solution shear coating without pulse voltage was used to prepare the photosensitive active layer. The prepared organic photovoltaic device was tested under the illumination of an AAA solar simulator. The spectral distribution of the solar simulator was AM1.5G, and the illumination intensity was calibrated to 100mW / cm² using a standard silicon cell. 2 The open-circuit voltage (V) of the device was measured under the above conditions. OC ) = 0.842V, short-circuit current (J) SC = 25.4 mA / cm 2 The fill factor (FF) is 77.9%, and the photoelectric conversion efficiency (PCE) is 16.4%. Figure 6 As shown.
[0073] Comparative Example 2
[0074] Organic photovoltaic devices are prepared according to the device structure described in Example 1 and the method for preparing high-efficiency organic solar cell devices by electric field modulation technology for shear coating of solution in air as described in Comparative Example 1, the difference being:
[0075] In step (3), the photosensitive active layer was prepared by solution shear coating without pulse voltage, and step (5) was not performed.
[0076] The distribution morphology of the acceptor components on the surface of the photosensitive active layer was observed using light-induced atomic force microscopy, such as... Figure 7 As shown, non-fullerene small molecule acceptor materials form large aggregate morphologies, which are not conducive to the dissociation of photogenerated excitons and can lead to severe charge recombination, thus affecting the photovoltaic performance of organic solar cell devices.
[0077] Table 1. Performance of organic solar cells prepared in Example 2 and Comparative Example 1
[0078]
[0079] By comparing the data in Table 1, it can be seen that among the organic photovoltaic devices prepared by different methods, the fill factor and photoelectric conversion efficiency of the devices prepared by pulsed electric field assistance are significantly improved compared with the original method, thus realizing high-efficiency organic solar cells.
Claims
1. An organic solar cell device prepared by electric field- assisted solution shear coating, characterized in that, From bottom to top, it comprises a glass substrate, an indium tin oxide transparent conductive film, a hole transport layer, an organic light-sensitive active layer, an electron transport layer, and a top electrode, wherein the organic light-sensitive active layer comprises a polymer donor material and a non-fullerene acceptor material.
2. The organic solar cell device prepared by the electric field- assisted solution shear coating according to claim 1, characterized in that, The polymer donor material in the organic light-sensitive active layer is PM6, and the non-fullerene acceptor material is BTP-eC9, and the mass ratio of the two is 1:1.
2. Preferably, the glass substrate is attached with an ITO transparent conductive film to form a transparent conductive substrate. The thickness of the ITO transparent conductive film is 130 nm; the hole transport layer material is PEDOT:PSS, and the thickness is 30 nm; the thickness of the organic light-sensitive active layer is 120 nm; the electron transport layer material is PDINN, and the thickness is 5 nm; and the top electrode material is silver, and the thickness is 100 nm.
3. The method of claim 1-2 for fabricating an organic solar cell device by electric field assisted solution shearing coating, characterized in that, The steps include the following: (1) cleaning the transparent conductive substrate, which is a glass substrate attached with an ITO transparent conductive film; (2) preparing a hole transport layer PEDOT:PSS film on the transparent conductive substrate obtained in step (1) by using a conventional preparation method; (3) preparation of an organic active layer film, including: a. using a high-precision electronic balance to weigh and mix 10 mg of PM6 and 12 mg of BTP-eC9, then adding 1 mL of high-purity o-xylene solvent to the obtained mixture, and placing it on a magnetic stirrer that can be heated, stirring at 80℃ for 2.5h to obtain a PM6:BTP-eC9 blend solution with a total concentration of 22mg / mL; b. using a high-precision pipette to add 2.50μL of 1,8-diiodooctane additive to the PM6:BTP-eC9 blend solution obtained above, and after continuing to stir for 30min, a fully dissolved mixed solution of PM6:BTP-eC9 with a mass ratio of 1:1.2 is obtained; c. using a spin coater to coat the mixed solution prepared in step b on the substrate with a hole transport layer obtained in step (2) in an air environment under the action of an externally applied pulsed polarization electric field; (4) depositing an electron transport layer PDINN film on the organic light-sensitive active layer; (5) evaporating the metal electrode material on the electron transport layer.
4. The method of claim 3, wherein the organic solar cell device is prepared by an electric field-assisted solution shearing coating method. In step c of step (3), the externally applied pulsed polarization electric field is achieved by connecting a pulsed polarization voltage source to the doctor blade of the solution shear coater and the substrate stage.
5. The method of claim 3, wherein the organic solar cell device is prepared by an electric field-assisted solution shearing coating method. In step c of step (3), the substrate temperature is 80℃, the gap between the doctor blade and the substrate is 150μm, the moving speed of the doctor blade relative to the substrate is 25mm / s, and the amount of mixed solution used in the gap between the doctor blade and the substrate is 30μL, and under these conditions, the thickness of the active layer obtained is 120nm.
6. The method of claim 3, wherein the organic solar cell device is prepared by an electric field-assisted solution shearing coating method. The voltage provided by the pulse power source in step c of step (3) is 10-10kV, 200Hz, square wave, and the duty cycle is 1-99%.
7. The method of claim 6, wherein the organic solar cell device is prepared by an electric field-assisted solution shearing coating method. The voltage provided by the pulse power source in step c of step (3) is 100V, 200Hz, square wave, and the duty cycle is 50%.
8. The method of claim 3, wherein the organic solar cell device is prepared by an electric field-assisted solution shearing coating method. In the step (1), the transparent conductive substrate is sequentially cleaned with precision electrical cleaner, deionized water, acetone, anhydrous ethanol and isopropanol in an ultrasonic machine for 10 minutes respectively, and then dried with high-purity nitrogen; the dried transparent conductive substrate is placed in a UV-ozone cleaner for 30 minutes; Preferably, in the step (2), a layer of hole transport layer material PEDOT:PSS with a thickness of 30 nm is spin-coated on the cleaned transparent conductive substrate using a spin coater in air, and then the substrate with the hole transport layer material is placed on a hot stage at 150°C for annealing for 15 minutes.
9. The method of claim 3, wherein the organic solar cell device is prepared by an electric field-assisted solution shearing coating method. In the step (4), PDINN is dissolved in high-purity methanol solvent (AR>99%, concentration 1.5 mg / mL), and the prepared PDINN solution is placed on a magnetic stirring table and stirred at room temperature for 2 hours to obtain a fully dissolved PDINN solution; The fully dissolved PDINN solution is spin-coated on the organic photoactive layer annealed in the step (3) using a spin coater.
10. The method of claim 3, wherein the organic solar cell device is prepared by an electric field-assisted solution shearing coating method. In step (5), the substrate with the hole transport layer / organic photoactive layer / electron transport layer obtained in step (4) is moved into a physical vapor deposition chamber, and after the vacuum system is started and the pressure in the chamber is reduced to 2.5 x 10 -4 Pa, a silver target is heated to prepare an Ag electrode on the substrate, and the thickness of the electrode is 100 nm.